Indeks Stakeholders Pengelolaan Daerah Aliran Sungai dengan Pendekatan KISS di Indonesia - Sriyana, Ignatius (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Integrated watershed management (IWM) using KISS (coordination, integration, synchronisation, and synergy) method is believed to be the answer for problems lingering the integrated watershed management in Indonesia. How successful the management is depends on how capable of stakeholders are to performing coordination, integration, synchronisation, and synergy in managing the watershed. This study aimed at measuring the rates of coordination, integration, synchronisation, and synergy performed by each stakeholder by applying an "Index Rate" instrument. Research findings revealed that, simultaneously, the coordination, integration, synchronisation, and synergy obtained by the watershed management stakeholders resulted in a moderate rate (71.4). Partially, the rates obtained were as follows: moderate coordination (72.69); moderate integrity (72.50); moderate synchronisation (70.34); and moderate synergy (70.05).